2017
DOI: 10.5944/openpraxis.9.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Student Views on the Cost of and Access to Textbooks: An Investigation at University of Otago (New Zealand)

Abstract: The rising cost of textbooks is influencing students' choice of courses, as well as the quality of their learning experience once they are enrolled in a course, according to recent studies. This paper builds on those studies by exploring the possible effects that textbook costs may be having on study behaviours of students at one New Zealand tertiary institution: University of Otago. Perceptions of undergraduate students (n-811) about cost of, and access to, textbooks and possible influences on their study beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…They could learn this by observing their own study habits, the practices of students around them (particularly when taking courses with a mix of first year and upper-class students), and the way their professors appear to value required texts. This observation that students may learn not to buy required texts over time has been noted in other research as well (Stein et al, 2017).…”
Section: Cost/value Reinforcement Cyclesupporting
confidence: 74%
“…They could learn this by observing their own study habits, the practices of students around them (particularly when taking courses with a mix of first year and upper-class students), and the way their professors appear to value required texts. This observation that students may learn not to buy required texts over time has been noted in other research as well (Stein et al, 2017).…”
Section: Cost/value Reinforcement Cyclesupporting
confidence: 74%
“…Examining student perceptions of textbook cost is a relatively new endeavor in this area, and much of the focus is on comparing the quality or efficacy of traditional textbooks to OER. There are a handful of studies that explore student perceptions of impact of the cost of course materials on their quality of life; how cost impacts student success; and how students describe their engagement with course materials (Brandle et al, 2019;Martin, Belikov, Hilton, Wiley & Fischer, 2017;Stein, Hart, Keaney & White, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, student participants from the BYU study felt that the cost of textbooks had a negative impact on their academic success, with 66% stating that they had not purchased a textbook because of its price and 47% indicating that not purchasing a textbook had negatively impacted their grade in a course (Martin et al, 2017). Stein et al (2017) conducted a study at a university in New Zealand and also found that more than half of their respondents indicated that they felt that the cost of textbooks has had a negative impact on their academic success. The Student Public Interest Research Groups (PIRGs) conducted a large-scale survey with 2,039 students from over 150 different universities (Selnack, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another survey (n = 3115), students at Brigham Young University indicated that they would spend money saved from not purchasing a textbook on housing (28.86%) and food (28.32%) (Martin, Belikov, Hilton, Wiley & Fisher, 2017). Students report that they have delayed or decided against making a textbook purchase despite anxiety over how that choice might negatively affect their course grade (Senack, 2014;Hilton, 2016;Martin et al, 2017;Stein, Hart, Keaney & White, 2017;Jhangiani & Jhangiani, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%